Personalized Al-Quran Memorization Testing System Using Group Decision Support System - Rajagede*, Rian Adam; Hisyam, Yuanda Hanif; Yulianto, Muhammad Ichlasul Amal; Ridwanto, Farid Amin; Putranto, Alfian Try; Danar, Muhammad Rifqi Fatchurrahman Putra (Aceh International Journal of Science and Technology, 2021)
This paper focuses on using self-compacting concrete (SCC) as a material in the repair technique given the advantages it presents in the fresh state, namely: stability, homogeneity, and deformability, because it perfectly matches the shapes of the surfaces to be repaired. The interest is mainly focused on the evaluation of bond strength at the interface: Repair/Substrate. The assessment is made via a repair applied to a half-cylinder of the ordinary concrete substrate (OC), by using as a repair material two classes of self-compacting concrete (SCC) of different strength (30 and 40 MPa), the interface bond strength obtained in this case is compared to that of a half-cylinder (BO) repaired with vibrated concrete (OVC) used as a reference control concrete. The rheological properties of the (SCC) used were determined with the aid of the Slump-flow, L-Box, V funnel, and stability under sieve tests. Mechanical properties include compressive strength, and tensile strength. The test to assess the interface bond strength of the specimens is based on a splitting tensile test (indirect tensile). Finally, to determine the type of failure produced after the test. The results obtained showed that self-compacting concrete appears to be a very promising material in the repair and rehabilitation of concrete structures. SCC offers good interfacial bonding and therefore gives satisfactory interface bond strengths.